Effect of regional trauma centralization on volume, injury severity and outcomes of injured patients admitted to trauma centres. Issue 8 (July 2014) - Metcalfe, D.; Bouamra, O.; Parsons, N. R.; Aletrari, M.‐O.; Lecky, F. E.; Costa, M. L.
<x xml:space="preserve">Abstract</x> Background Centralization of complex healthcare services into specialist high‐volume centres is believed to improve outcomes. For injured patients, few studies have evaluated the centralization of major trauma services. The aim of this study was to evaluate how a regional trauma network affected trends in admissions, case mix, and outcomes of injured patients. Methods A retrospective before–after study was undertaken of severely injured patients attending four hospitals that became major trauma centres (MTCs) in March 2012. Consecutive patients with major trauma were identified from a national registry and divided into two groups according to injury before or after the launch of a new trauma network. The two cohorts were compared for differences in case mix, demand on hospital resources, and outcomes. Results Patient volume increased from 442 to 1326 (200 per cent), operations from 349 to 1231 (253 per cent), critical care bed‐days from 1100 to 3704 (237 per cent), and total hospital bed‐days from 7910 to 22 772 (188 per cent). Patient age increased on MTC designation from 45·0 years before March 2012 to 48·2 years afterwards (P = 0·021), as did the proportion of penetrating injuries (1·8 versus 4·1 per cent; P = 0·025). Injury severity fell as measured by median Injury Severity Score (16 versus 14) and Revised Trauma Score (4·1 versus 7·8). Fewer patients required secondary transfer to a MTC from peripheral hospitals (19·9 versus 16·1 per cent; P = 0·100). There were no significant differences in total duration of hospital stay, critical care requirements or mortality. However, there was a significant increase, from 55·5 to 62·3 per cent (P < 0·001), in the proportion of patients coded as having a 'good recovery' at discharge after institution of the trauma network. Conclusion MTC designation leads to an increased case volume with considerable implications for operating theatre capacity and bed occupancy. Although no mortality benefit was demonstrated within 6 months of establishing this trauma network, early detectable advantages included improved functional outcome at discharge.